Sustainable antibiofilm self-assembled colloidal systems - Morán, Diana; Saweres-Argüelles, Clara; Marchiano, Verdiana; Bazsefidpar, Shayesteh; Serrano-Pertierra, Esther; Matos, Maria; Gutierrez, Gemma; Blanco-López, Maria Carmen (Frontiers in Soft Matter, 2022)
Biofilms find a favourable environment in industrial processes such as food, cosmetic or medical prothesis and devices, being responsible of around 80% of human bacterial infections. Prevention and/or eradication of microorganism’ films is a worldwide need. There is an increasing interest on the finding and use of novel antimicrobial compounds without side effects. An additional challenge is to fight the antimicrobial resistance that some bacteria and microorganisms develop with traditional antibiotics. And in recent years, sustainability and natural source of the antibiofilms chemical principles are also a priority demand. Colloidal systems such as vesicles, particles suspensions or emulsions are being an increasing tool used for biocompounds delivery due to the protection that they offer to the compound encapsulated versus external factors, and their possibility to be used as target delivery systems. During last decade, these types of systems have been widely used for the encapsulation of traditional and novel compounds with antimicrobial properties. The present article summarizes different types of natural compounds tested versus several types of bacteria and its feasibility to be encapsulated in different types of colloidal systems.